Mind the gap: A multi-country BVAR benchmark for the Eurosystem projections - Elena Angelini; Magdalena Lalik; Michele Lenza; Joan Paredes (European Central Bank (ECB), 2019)
The Eurosystem staff forecasts are conditional on the financial markets, the global economy and fiscal policy outlook, and include expert judgement. We develop a multi-country BVAR for the four largest countries of the euro area and we show that it provides accurate conditional forecasts of policy relevant variables such as, for example, consumer prices and GDP. The forecasting accuracy and the ability to mimic the path of the Eurosystem projections suggest that the model is a valid benchmark to assess the consistency of the projections with the conditional assumptions. As such, the BVAR can be used to identify possible sources of judgement, based on the gaps between the Eurosystem projections and the historical regularities captured by the model.
Keywords: C52; C53; E37; 330; Multi-country model; cross-checking; conditional forecast; euro area